Evaluation of The Satisfaction Level of Outpatient Patients With The Quality of Pharmaceutical Services in UPTD Public Health Centre DTP Benery Meriah District Bandar Regency in 2020 - Muflih; Rizkani (Pena Cendekia Insani, 2021)
The quality of health services in Indonesia is still not in line with people's expectations, even though in Indonesia it provides health insurance for the underprivileged or the poor. Currently, patient satisfaction services are the main focus in the context of health services. factors and listen to patient desires. at UPTD Public Health Centre DTP Bandar, Bandar Subdistrict, Bener Meriah Regency in 2020. Methods; The type of research conducted is cross sectional, the sampling technique is accidental sampling using a questionnaire with a total sample of 95 outpatients. Results; The results of the research on each indicator obtained the following percentages where based on patient satisfaction the majority was quite satisfied at 58.9%. The majority of physical evidence said 34.7% was sufficient, the majority said sufficient reliability was 46.3%. The majority response was good at 48.4%. The majority concern was good at 46.3%, while the majority assurance indicator said it was not good at 38.9%.